Patient‐reported outcome measures for emotional functioning in cancer patients: Content comparison of the EORTC CAT Core, FACT‐G, HADS, SF‐36, PRO‐CTCAE, and PROMIS instruments. Issue 4 (19th February 2023) - Rothmund, Maria; Pilz, Micha J.; Egeter, Nathalie; Lidington, Emma; Piccinin, Claire; Arraras, Juan I.; Grønvold, Mogens; Holzner, Bernhard; van Leeuwen, Marieke; Petersen, Morten Aa.; Schmidt, Heike; Young, Teresa; et al.
Abstract: Background: Cancer and its treatment can have substantial impact on patients' emotional functioning. Several patient‐reported outcome measures (PROMs) assessing emotional functioning are available, but differences in content limit the comparability of results. To better understand conceptual (dis)similarities, we conducted a content comparison of commonly used PROMs. Methods: We included emotional functioning items, scales, and item banks from the EORTC CAT Core, EORTC QLQ‐C30, FACT‐G, Hospital anxiety and depression scale (HADS), SF‐36, PRO‐CTCAE, and PROMIS (item banks for anxiety, depression, and anger). Item content was linked to the International Classification of Functioning, Disability, and Health (ICF) and a hierarchical framework established for PROMIS. Single items could be coded with more than one ICF category but were solely assigned to one facet within the PROMIS framework. Results: The measures comprise 132 unique items covering the ICF components 'Body functions' (136/153 codings, 88.9%) and 'Activities and participation' (15/153, 9.8%). Most ICF codings (112/153, 73.2%) referred to the third‐level category 'b1528 Emotional functions, other specified'. According to the PROMIS framework 48.5% of the items assessed depression (64/132 items), followed by anxiety (41/132, 31.1%) and anger (26/132, 19.7%). The EORTC measures covered depression, anxiety, and anger in a single measure, while the PROMIS inventory provides separate item banks for these concepts. The FACT‐G, SF‐36, PRO‐CTCAE and HADS covered depression and anxiety, but not anger. Conclusion: Our results provide an in‐depth conceptual understanding of selected PROMs and important qualitative information going beyond psychometric evidence. Such information supports the identification of PROMs for which scores can be meaningfully linked with quantitative methods.